Answer:
Below
Explanation:
● x-20 = y+20 (1)
● 2(y-22) = x+22 (2)
This is a system of simulataneous equations
Let's simplify the expressions first
● x -20 = y + 20 (1)
Add 20 to both sides
● x -20 + 20 = y+20 +20
● x = y + 40 (1)
● 2(y-22) = x+22 (2)
● 2y - 44 = x +22
Substrat 22 from both sides
● 2y-44-22 = x+22-22
● 2y -66 = x (2)
This is the new system:
● x = y+40 (1)
● x = 2y-66 (2)
Substract (2) from (1)
● x-x = y+40-(2y-66)
● y+40-2y+66 = 0
● -y +106 = 0
● y = 106
Replace y with 106 in (1)
● x = y +40
● x = 106+40
● x = 146
So the solutions are (146,106)